Development of nanostructured nickel oxide thin film matrix by rf sputtering technique for the realization of efficient bioelectrode. (December 2018) - Dhull, Nidhi; Kaur, Gurpreet; Gupta, Vinay; Tomar, Monika
Abstract: In the present work, RF magnetron sputtering technique has been exploited with varied deposition parameters (optimized parameters: sputtering pressure = 20 mT, 100% O2 gas ambient, without any substrate heating) to develop nanostructured NiO thin film matrix with increased surface roughness (5.09 nm) and good charge transfer properties for efficient detection of cortisol. Electrochemical and electrical studies have been performed to determine charge communication characteristics and conductivity of the prepared NiO thin film that could yield enhanced biosensing response properties. The biosensing response has been studied on the optimized parameters using cortisol as a test analyte and a relatively high sensing response of 14 μA (ug/mL) −1 has been obtained for the optimized NiO matrix-based electrodes (Cortisol-Ab/NiO/ITO). Highlights: NiO thin films were prepared using rf magnetron sputtering under varying deposition parameters. Effect of deposition parameters on charge transfer characteristics of NiO thin film have been studied. Optimized NiO thin film has been employed as a bioelectrode. Relatively high biosensing response (14 μA (ug/mL) -1 ) towards cortisol as a test analyte has been obtained.